Impact of winter roads on boreal peatland carbon exchange - Maria Strack; Divya Softa; Melanie Bird; Bin Xu (Global Change Biology, 2018)
Across Canada's boreal forest, linear disturbances, including cutlines such as seismic lines and roads, crisscross the landscape to facilitate resource exploration and extraction; many of these linear disturbances cross peatland ecosystems. Changes in tree canopy cover and the compression of the peat by heavy equipment alter local thermal, hydrological, and ecological conditions, likely changing carbon exchange on the disturbance, and possibly in the adjacent peatland. We measured bulk density, water table, soil temperature, plant cover, and CO 2 and CH 4 flux along triplicate transects crossing a winter road through a wooded fen near Peace River, Alberta, Canada. Sample plots were located 1, 5, and 10 m from the road on both sides with an additional three plots on the road. Productivity of the overstory trees, when present, was also determined. The winter road had higher bulk density, shallower water table, higher graminoid cover, and thawed earlier than the adjacent peatland. Tree productivity and CO 2 flux varied between the plots, and there was no clear pattern in relation to distance from the road. The plots on the winter road acted as a greater CO 2 sink and greater CH 4 source compared to the adjacent peatland with plots on the winter road emitting on average (standard error) 479 (138) compared to 41 (10) mg CH 4 m −2 day −1 in the adjacent peatland. Considering both gases, global warming potential increased from 70 to 250 g CO 2 e m −2 year −1 in the undisturbed area to 2100 g CO 2 e m −2 year −1 on the winter road. Although carbon fluxes on any given cutline through peatland will vary depending on level of compaction, line width and vegetation community shifts, the large number of linear disturbances in Canada's boreal forest and slow recovery on peatland ecosites suggest they could represent an important anthropogenic greenhouse gas source.